2004
DOI: 10.1140/epjb/e2004-00172-3
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature nonequilibrium dynamics in transverse Ising spin glass

Abstract: The real part of the time-dependent ac susceptibility of the short-range Ising spin glass in a transverse field has been investigated at very low temperatures. We have used the quantum linear response theory and domain coarsening ideas of quantum droplet scaling theory. It is found that after a temperature quench to a temperature which is less than the spin glass transition temperature the ac susceptibility decreases with time elapsed after the initial quench towards equilibrium approximately logarithmically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…P. Svedlindh et al [35] have investigated the behavior of and have found that decay is close to a logarithmic one. Shins et al [22] also show that susceptibility decays with time in a nearly logarithmic way.…”
Section:  mentioning
confidence: 93%
See 1 more Smart Citation
“…P. Svedlindh et al [35] have investigated the behavior of and have found that decay is close to a logarithmic one. Shins et al [22] also show that susceptibility decays with time in a nearly logarithmic way.…”
Section:  mentioning
confidence: 93%
“…The natural basis for the interpretation of aging is based on coarsening ideas of a slow domain growth of a spin-glass type ordered phase [8,13,14]. A large attention in the last decade was paid to the spin glasses representing a model systems for study of non-equilibrium dynamics providing a measure of processes causing the aging: the magnetic susceptibility [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%